Adenosine Receptors as Neuroinflammation Modulators: Role of A(1) Agonists and A(2A) Antagonists - Martí Navia, Aleix (Cells, 2020)
The pathological condition of neuroinflammation is caused by the activation of the neuroimmune cells astrocytes and microglia. The autacoid adenosine seems to be an important neuromodulator in this condition. Its main receptors involved in the neuroinflammation modulation are A(1)AR and A(2A)AR. Evidence suggests that A(1)AR activation produces a neuroprotective effect and A(2A)ARs block prevents neuroinflammation. The aim of this work is to elucidate the effects of these receptors in neuroinflammation using the partial agonist 2′-dCCPA (2-chloro-N(6)-cyclopentyl-2′-deoxyadenosine) (C1 K(i)A(1)AR = 550 nM, K(i)A(2A)AR = 24,800 nM, and K(i)A(3)AR = 5560 nM, α = 0.70, EC(50)A(1)AR = 832 nM) and the newly synthesized in house compound 8-chloro-9-ethyl-2-phenethoxyadenine (C2 K(i)A(2A)AR = 0.75 nM; K(i)A(1)AR = 17 nM and K(i)A(3)AR = 227 nM, IC(50)A(2A)AR = 251 nM unpublished results). The experiments were performed in in vitro and in in vivo models of neuroinflammation. Results showed that C1 was able to prevent the inflammatory effect induced by cytokine cocktail (TNF-α, IL-1β, and IFN-γ) while C2 possess both anti-inflammatory and antioxidant properties, counteracting both neuroinflammation in mixed glial cells and in an animal model of neuroinflammation. In conclusion, C2 is a potential candidate for neuroinflammation therapy.